Mother’s Perception of Social Skills of Children With Autism in The Special Needs Therapy Center in Makassar - Bandung, Dewita Amanda; Seniwati, Tuti; Nurfadhilah, Nurfadhilah (Indonesian Contemporary Nursing Journal (ICON Journal), 2017)
Introduction: Impaired social ability is the main problem faced by children with autism according to Diagnostic and Statistical Manual (DSM-IV), which may have an impact on the cognitive, affective, and behavioural abilities if left untreated. Aim: This study aims to analyse social skills aspects of children with autism who undergo therapy in special needs children therapy center in Makassar. Method: The descriptive analytic method with cross sectional design was applied in this study. The instrument used was the TRIAD Social Skills Assessment (TSSA)-Assessing Children with Autism Spectrum Disorder questionnaire. The questionnaires were given to 42 respondents who is the mother of children with autism spectrum disorder symptom and is undergoing therapy in special needs children therapy center in Makassar. Result: The results of this study found that children have affective understanding ability in medium category (59.5%), initiating interactions ability are in medium category (59.5%), responding to the beginning of the interaction are in the medium category (66.7%), and ability to maintain interaction aspect are in medium category (57.1%). Conclusions: Mother with autism children who undergo therapy in special needs children therapy center in Makassar mostly have medium social skills. Therefore, it is expected that parents and therapists can provide support in improving the existing therapy program to deal with social skills of children with autistic disorder.